FAKTOR SOSIAL EKONOMI YANG BERHUBUNGAN DENGAN TINGKAT ADOPSI TEKNOLOGI USAHATANI PADI LAHAN PASANG SURUT - Priyono, Basuki Sigit; Sumantri, Bambang; Suwarni, Anna (Jurnal AGRISEP, 2004)
This Research  was aimed  to describ sources of family income  from paddy  farm, non paddy  farm, livestock and estimated  contribution  of paddy  revenue to total family income. This research  conducted  in the Srikaton village, Muara Padang -  Musi Banyuasin District South Sumatera.  The sudy revealed that involved frequency in extention  activities  and farm   experience  related to farmer adoption level.  The revenue  from paddy  farm is Rp 7.347.142,86  and give contribution  of 12,92 % to total family income.